Analysis of Islamic website design. (1st January 2012) - Badi, Maimona J.; Zeki, Akram M.
This article presents and analyses the findings regarding the utility of Islamic websites in terms of messages, credibility, standardisation, acceleration, printability, and distribution of terminologies. According to Leavitt and Shneiderman (2006), designers should make every attempt to reduce the user's workload by taking advantage of the computer's capabilities. Users will make the best use of websites when information is displayed in a directly usable format and content organisation is highly intuitive. The data is gathered from feedback to a questionnaire distributed to respondents from three faculties, namely ICT, engineering, and IRKHS students in various levels of university education. The data collected is based on five selected Islamic websites, namely islamway.com, islamweb.net, islamonline.net, islam-qa.com, and islamtoday.net.